(Attending analysis and synthesis in Descartes philosophy) (Journal of the College of Basic Education, 2022)
Analysis and synthesis is a scientific approach followed by many scientists and philosophers, including Descartes, as this approach was adopted in order to reach the accuracy and certainty of analysis when Descartes put things back to their simple natures and composition is the process of building these simple natures and forming them in order to reach clarity and distinct. Descartes has applied this approach to most of the ideas presented in his philosophy, where he tried to make analysis and synthesis basic rules in all aspects of human life in knowledge and in the physical formation of the person and even in the behavioral-ethical aspect of his practical life, so he stated in his writings(the mind the fairest division among people) we must use it best in coexistence with life and that is by showing its capabilities and capabilities ,and Descartes has taken analysis as a way to reach accuracy and certainty. In my research, presented some readings of Descartes's books in which I explained the most prominent topics the manifest the presence of analysis and synthesis. My readings have been devoted to :1-an essay on the method. 2-Hadith tariqat. 3-Rules for guiding thought. 4-principles of philosophy . synthesis I found that Descartes was able to show the importance of presence of analysis and synthesis by focusing on the mind and explaining its role and importance in analyzing and building ideas that are in harmony with each in order to reach accuracy and certainty. The mind contains tremendous capabilities that help it to construct the cognitive-scientific so that it can analyze acertain idea into its main elements and then reconstruct it tightly, and this is what Descartes did in his approach that relies on intuition and deduction the will lead him to mathematical science and thus formulate accurate mathematical laws. Add to that Descartes's interest in attending analysis and synthesis, not human knowledge, but rather an extension to the organic and behavioral aspect of the human being, where he was able to analyze the structures of human organs form the flow of blow and the work of the heart muscle, arteries ,veins and other organs. Members that contributed to the formation of the human body in way it is now. As for the moral aspect, he has set ethical rules, if person works with them, he is to reach the synthesis of happiness, and among these rules is to apply the laws of his country and be more determined in the completion of his work and strive to triumph over himself, and thus reach happiness, which is the ultimate goal of every human being. But this happiness is not complete except through knowing God is true knowledge, because knowledge because knowledge of God brings us to certainty, and the universe if we make it with all its celestial bodies, stars and planets belong to the creator of the universe, which is God, and this is what Descartes mentioned in his book An article on the method and rules for guiding thought.Thus we witnessed how the presence of analysis and synthesis in Descartes's philosophy was in coherent manner in the human mind and throughout the universe, reaching the highest and highest and highest universes, which is the creator, glory be to him.